Implementation of Land Revenue for The Construction of Toll Road from Pandaan to Malang - Wicaksono, Moch.Yuris; Rokhim, Abdul; Muhibbin, Moh.; Limsira, Patthara (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to understand how landowners make payments for development according to Law No. 10. Law No. 2 of 2012 regarding the process of legal solution in case of land acquisition for public benefit development and right holders not accepting the decision and/or money amortization study. The research used in this article is legal research and the following points can be deduced: (1). Payments are made in accordance with Law No. 1. The